Learning deficits and early school leaving: Evidence from a longitudinal study in India - K. G. Santhya; Nicole A. Haberland; A. J. Francis Zavier (PLoS ONE, 2025)
Although the relationship between learning deficits (LD) and early school leaving (ESL) is extensively acknowledged in studies from the Global North, fewer studies from the Global South have examined this relationship. We examined the levels and patterns of ESL among adolescents, relationship between LD and ESL and the gender dimensions, if any, in this relationship in India. We used data from a state-representative longitudinal study of adolescents aged 10−19 in Bihar and Uttar Pradesh states of India, conducted in 2015−16 and 2018−19. Descriptive analysis drew on data from adolescents ever enrolled in school (N = 11,476) and multivariate analyses used data from adolescents enrolled in school at wave 1 (N = 9,169). We used discrete-time hazard and fixed effects regression models to examine the relationship between LD and ESL. The probability of ESL was 39%, with a higher probability for girls (42%) than boys (38%). Although learning levels improved over time, 53% of adolescents displayed moderate or severe LD. Discrete-time hazard models show that LD influenced the probability of ESL (β = 1.959, p < 0.001 for those with severe LD and β = 0.568, p < 0.001 for those with moderate LD). Learning deficits equally affected the probability of ESL among girls and boys. Fixed effects regression models reiterate these findings. Investment in improving foundational skills is paramount for preventing early school leaving for girls and boys. However, the potential benefits will only be fully realised with accompanying measures which address gendered beliefs and practices and premature transition to adult roles, enhance parental engagement and improve education systems.